PENINGKATAN PEMAHAMAN MASYARAKAT TENTANG PERLINDUNGAN HUKUM TERHADAP KORBAN TINDAK PIDANA KEKERASAN DALAM RUMAH TANGGA - Kusumah, Haidan Angga; Dwi Putri, Eriska Ginalita; Mulyadi, Andi (Legality : Jurnal Ilmiah Hukum, 2016)
Domestic violence is a social phenomenon that has lasted a long time in most households in Indonesia. Domestic violence cases dominating against women in Sukabumi. The number of domestic violence cases that occurred in Indonesia is a reflection of the failure of a family to build and maintain a household conditions conducive and comfortable for each family member who took refuge in it. People still think that domestic violence is not a form of crime, is still considered taboo, and is a private matter that should not be to tell. the role performed by the College in providing education to rural communities Padaasih Cisaat about domestic violence and also how the socialization of the Law of the Republic of Indonesia No. 23 Year 2004 concerning the Elimination of Domestic Violence.